Concerns and professional development needs of faculty at King Abdul-Aziz University in Saudi Arabia in adopting online teaching - Kamal, Bakor (Kansas State University, 2013)
The purpose of this study was to investigate concerns regarding the adoption of online teaching as expressed by faculty and instructors in six departments in the College of Arts and Humanities at King Abdulaziz University. Additionally, it investigated faculty professional development needs in adopting online teaching. The data in this study were obtained from 147 faculty members (response rate 63.9%). A non-experimental, cross-sectional survey design was used, incorporating the Stages of Concern Questionnaire. The data were analyzed using quantitative measures (descriptive data analysis and inferential analysis). This study utilized the Concerns Based Adoption Model as its theoretical framework. King Abdulaziz University faculty Stages of Concerns findings showed a mean score percentile of 87% of them as Unconcerned. The Informational stage showed a mean score percentile of 72%, and the Personal stage was the third highest with a mean score percentile of 70%. Refocusing, Collaboration, and Management were the fourth, fifth, and sixth highest stages of concern. The Consequence stage was the lowest stage of concern. The Stages of Concern Questionnaire had concerns that were generally aligned to nonusers or users who sometimes implement parts of online teaching. The data analysis regarding the participants’ personal characteristics indicated that their concerns in adopting online teaching were not influenced by their age, country of graduation, or years of teaching experience. A statistically significant difference was found in the participant concerns in adopting online teaching by gender, p<.05. The significance differences were found in stage one (Informational) (p<.05), stage two (Personal) (p<.01), and stage six (Refocusing) (p<.001). Likewise, the data analysis regarding the participants’ contextual characteristics indicated that their concerns in adopting online teaching were not influenced by their department or academic rank. A statistically significant difference was found in the participants’ concerns in adopting online teaching based on administrative support, p<.05. The significances were found in stages zero (Unconcerned) (p<.05) and three (Management) (p<.01). The data analysis regarding the technographic characteristics also indicated a statistically significant influence of participants' prior instructional technology use and technology-related professional development on their use of technology in teaching. The significance values were .000, .006, .009, and .030. The study concludes with recommendations for King Abdulaziz University regarding faculty adoption of online teaching and recommendations for future studies focused on professional development programs and the adoption of online teaching in King Abdulaziz University as well as in other Saudi universities.
Keywords: Educational technology; Concerns; Concerns Based Adoption Model; Online Education; Saudi Arabia; Professional development; Online teaching; Education, Technology (0710); Instructional Design (0447); Middle Eastern Studies (0555)